Ideal presevation of Amniotic memebrane to be used in ocular surface - Shah, Sangeeta (Nepalese Journal of Ophthalmology, 2016)
According to the author Amniotic membrane was prserved in 100% glycerol for 3 months in whatman filter paper at the temperature of 4 degree.